Development of Android-Based Augmented Reality Learning Media on the Human Respiratory System to Improve Student Learning Outcomes - Rosyid, Yusuf Rosyid Ridho; Setyasto, Novi (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to develop Android-based augmented reality learning media for the science subject, specifically on the human respiratory system for grade V students at SDIT Sultan Agung 05. This research employs a Research and Development (R&D) approach using the Borg and Gall development model. The subjects of this study include validation test subjects consisting of material experts and media experts, and trial subjects consisting of grade V teachers and 27 grade V students. Data collection techniques used are observation, interviews, questionnaires, documentation, and tests (pretest and posttest). The results indicate that the Android-based augmented reality learning media is rated "very feasible" by both material and media experts. The responses from teachers and students are very positive, with an average percentage of 88%, indicating practicality. The pretest and posttest scores showed an average increase of 33.37 with an N-gain of 0.73, categorized as high. This indicates that the Android-based augmented reality learning media is feasible, practical, and effective in improving student learning outcomes in the science subject of the human respiratory system